Propuesta de gestión de mantenimiento para una flota de transporte terrestre - Díaz Cavero, Thaejannet Jeanneth Sennth (2016)
At present, companies, regardless of where they are developing, seek to increase their profits from their sales increase or decrease and control their costs and expenses. Therefore, they are in a constant period continues to apply better quality tools, processes and implementing standardized indicators in their critical processes. Mostly these efforts are focused on the core business areas as areas of commercial, operations and more. However, there are new approaches that seek to optimize the support areas such as accounting, human resources, maintenance and others. This proposed improvement arises reduce the costs of logistics company optimizing the use of third-party resources through increased availability of machinery belonging to the organization. Consequently, preventive maintenance is planned to make the machinery in order to reduce the hours of corrective maintenance. To do this, those responsible for the activities within the area, the procedures to perform preventive and corrective maintenance as indicators to manage work will be defined. Finally, the economic impact on the company in a time of three years will be assessed.